The Influence of Corporate Social Responsibility on Customer Perspective in Private Universities - Al-Hosaini, Fahmi Fadhl; Sofian, Saudah (International Journal of Economics and Financial Issues, 2015)
The goals of organizations, despite maximization of profits should be directed at satisfying customers, particularly with respect to societal values, purposeful and strategic business gains. Previous studies have been on enhancing the financial gains without adequate prospects for corporations’ responsiveness to their operational environment and customers. However, there are no substantial empirical studies on the influence of organizations corporate exercises, perceptions, and responsibility to those of customers’ satisfactions, principally when considered in the context of Private Universities (PUs). In this paper therefore, the effects of organization’s corporate social responsibility (CSR) on customer perspective (CP) was investigated with respect to Yemen’s PUs and Higher Education Institutions. A structured questionnaire using Partial Least Square-Structural Equation Modeling methodology was used for data collection; respondents were top-management staffs from these organizations. Results revealed that CSR has a positive influence on the Customer Perception of Yemen’s PUs. This study therefore justified the support and contribution to the dearth of knowledge on the impacts of CSR on organisational CP. Keywords: Corporate Social Responsibility; Customer Perspective; Private Universities; Higher Education Institutions; Structural Equation Modeling JEL Classifications: G30